Izabal, Gautemala (Cardinell-Vincent Co.)
On verso: The Ruins of Quirigua, Thoughtful countries never disdain the lessons of the past. Monuments, such as the ruins of Quirigua, are silent yet eloquent witnesses of the greatness and civilization of the primitive populations of Central America.